Study of the Characteristics Mechanical Damage and Constitutive Model of Crushed-Rocks from High-Grade Highway in Permafrost Region. (28th April 2022) - Zhang, Qinshuai; Wang, Qingzhi; Fang, Jianhong; Zhao, Xiangqing; Li, Jizhen; Li, Shuan
Abstract : Three types of rocks are selected to conduct uniaxial compression and microscope experimental to study the influences of freeze-thaw cycles on crushed-rocks from Gonghe-Yushu high-graded highway, which is the first high-grade highway built in permafrost regions in China. Using the hypothesis of Lemaitre's strain equivalence principle and a theoretical model of crushed-rock deterioration after freeze-thaw cycles was established and verified by the experimental data. The experimental results showed that with an increase of the number of freeze-thaw cycles, the microcracks of saturated red sandstone increased, and this phenomenon is not obvious on other rocks. Moreover, different degrees of spalling and cracks appeared, with common physical parameters gradually decreasing. The uniaxial compressive strength of rock decreases exponentially with the increase of the number of freeze-thaw cycles. The mechanism of the influence of freeze-thaw cycles on the fine structure of the three different crushed-rocks were then analyzed using SEM scanning. Freeze-thaw cycles weaken the connection between rock mineral particles and increase the surface micropores. The damage model of freeze-thaw and load can well describe the damage law of crushed-rocks.